2014
DOI: 10.1371/journal.pgen.1004215
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Regulon Evolution: Distinct Responses and Roles for the Identical OmpR Proteins of Salmonella Typhimurium and Escherichia coli in the Acid Stress Response

Abstract: The evolution of new gene networks is a primary source of genetic innovation that allows bacteria to explore and exploit new niches, including pathogenic interactions with host organisms. For example, the archetypal DNA binding protein, OmpR, is identical between Salmonella Typhimurium serovar Typhimurium and Escherichia coli, but regulatory specialization has resulted in different environmental triggers of OmpR expression and largely divergent OmpR regulons. Specifically, ompR mRNA and OmpR protein levels are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(152 citation statements)
references
References 87 publications
(133 reference statements)
5
142
2
Order By: Relevance
“…Experimental data demonstrating a response at the level of DNA supercoiling to variations in pH (Bang et al 2002;Karem and Foster 1993;Quinn et al 2014), temperature (Goldstein and Drlica 1984), osmotic pressure (Alice and Sanchez-Rivas 1997; Bordes et al 2003;Cheung et al 2003;Higgins et al 1988;Meury and Kohiyama 1992;O'Byrne et al 1992;Sheehan et al 1992), oxygen supply (Bebbington and Williams 2001;Cameron et al 2011Cameron et al , 2013Cortassa and Aon 1993;Dixon et al 1988;Dorman et al 1988;Malkhosyan et al 1991;Yamamoto and Droffner 1985), oxidative stress (Weinstein-Fischer et al 2000), nutrition (Balke and Gralla 1987), growth phase (Bordes et al 2003;Conter et al 1997), intracellular growth (Ó Cróinín et al 2006) and much more have been reported. A rapidly growing cell has different gene expression requirements to one that is in stationary phase and one that is undergoing a growth phase transition has yet another set of needs.…”
Section: An Environmentally Responsive Global Regulatory Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental data demonstrating a response at the level of DNA supercoiling to variations in pH (Bang et al 2002;Karem and Foster 1993;Quinn et al 2014), temperature (Goldstein and Drlica 1984), osmotic pressure (Alice and Sanchez-Rivas 1997; Bordes et al 2003;Cheung et al 2003;Higgins et al 1988;Meury and Kohiyama 1992;O'Byrne et al 1992;Sheehan et al 1992), oxygen supply (Bebbington and Williams 2001;Cameron et al 2011Cameron et al , 2013Cortassa and Aon 1993;Dixon et al 1988;Dorman et al 1988;Malkhosyan et al 1991;Yamamoto and Droffner 1985), oxidative stress (Weinstein-Fischer et al 2000), nutrition (Balke and Gralla 1987), growth phase (Bordes et al 2003;Conter et al 1997), intracellular growth (Ó Cróinín et al 2006) and much more have been reported. A rapidly growing cell has different gene expression requirements to one that is in stationary phase and one that is undergoing a growth phase transition has yet another set of needs.…”
Section: An Environmentally Responsive Global Regulatory Systemmentioning
confidence: 99%
“…Because they rely on DNA structure rather than the presence of a specific base sequence, indirect readout mechanisms of DNA binding offer a powerful means to drive the evolution of gene regulation (Xu et al 2014). Proteins like OmpR, with low requirements for specific base sequences in their binding sites but which are sensitive to the superhelicity of the binding site DNA, are well placed to recruit new genes to their regulons (Quinn et al 2014), including genes that arrive in the bacterial cell via horizontal gene transfer (Cordeiro et al 2011). …”
Section: Protein Binding As a Function Of Dna Topologymentioning
confidence: 99%
See 3 more Smart Citations